Identifikasi Dampak Penggunaan Sistem Informasi Rumah Sakit (SIRS) Terhadap Pelayanan Kesehatan Menggunakan Hot-Fit Model 2006 - Frendy Rocky Rumambi; Salahudin Robo; Citra Amalia (STMIK Budi Darma, 2020)
Hospital Information System (SIRS) is an integrated information system that aims to handle all hospital management processes, ranging from diagnostic services, medical data measures, medical records, pharmaceuticals, pharmaceutical warehouses, billing, personnel databases, payroll, and accounting to the control management. Based on Indonesian Constitution No. 44 Article 52 year 2009, paragraph 1 states that